DAJE NAJ
Oblicz mnożenie z algebry
dla wytłumaczenia a= 3 , b= -2
a) 4(a+2b-4) - 3(3a-b-4) - (2-a) =
b) -3(4-5b+a) + 2(-5+a-b) - (-3+b) =
c)⅓ (b- 9+ 15b) + (¼(20a-4b) + ½ (6a-8) =
d) 0,3(2a-3b+5) - 0,7(10-4a+5b) - 18 =

dla wytłumaczenia a= 3 , b= -2

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-12T22:03:33+02:00
A)4(a+2b-4)-3(3a-b-4)-(2-a) =4a+8b-16-9a+3b+12-2+4=
-5a+11b-2=-5*3+11*(-2)-2=-15-22-2=-39
b) -3(4-5b+a)+2(-5+a-b)-(-3+b) =-12+15b-3a+10+2a-2b+3-b=
1+12b-a=1+12*(-2)-3=1-24-3=-26
c)⅓ (b- 9+ 15b)+ (¼(20a-4b)+ ½ (6a-8) =⅓b-3+5b+5a-b+3a-4=
4⅓b-7+8a=¹³/₃*(-2)-7+8*3=-²⁶/₃-7+24=8⅔+17=25⅔
d) 0,3(2a-3b+5) - 0,7(10-4a+5b)-18 =0,6a-0,9b+1,5-7+2,8a-3,5b-18=
3,4a-4,4b-23,5=3,4*3-4,4*(-2)-23,5=10,2+8,8-23,5=-4,5


1 5 1
2010-04-12T22:11:11+02:00
A= 3 , b= -2

a)4(a+2b-4)-3(3a-b-4)-(2-a) =
4a+8b-16-9a+3b+12-2+a=
-4a+11b-6=
-4*3+11*(-2)-6=
-12-22-6=
-40

b) -3(4-5b+a)+2(-5+a-b)-(-3+b) =
-12+15b-3a-10+2a-2b+3-b=
-19+12b-a=
-19+12*(-2)-3=
-19-24-3=
-46


c)⅓ (b- 9+ 15b)+ (¼(20a-4b)+ ½ (6a-8) =
⅓b-3+5b+5a-b+3a-4=
-7+8a-13/3b=
-7+24-26/3=
77/3=25,6

d) 0,3(2a-3b+5) - 0,7(10-4a+5b)-18 =
0,6a-0,9b+1,5-7+2,8a-3,5b-18=
3,4a-4,4b-23,5=
3,4*3-4,4*(-2)-23,5=
10,2+8,8-23,5=
-4,5

1 5 1